The role of mental imagery as driver to purchase intentions in a virtual supermarket - Loureiro, S. M. C.; Correia, C.; Guerreiro, J. (Augmented reality and virtual reality: New trends in immersive technology, 2021)
This study aims to explore the role of mental imagery, product involvement and presence on emotions and purchase intentions. A quasi-experimental between-subjects design was implemented to test the proposed model. The quasi-experimental manipulation comprised a virtual grocery store, using VR. A quantitative approach was followed using a questionnaire to get data to test the model. The questionnaire was fulfilled after the 108 participants visualize the scenario through VR. The results reveal that all hypotheses are supported, expect H4. Product involvement is not associated to emotions.